2022
DOI: 10.3389/fnmol.2022.879146
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal ER-Signalosome Proteins as Early Biomarkers in Prodromal Alzheimer's Disease Independent of Amyloid-β Production and Tau Phosphorylation

Abstract: There exists considerable interest to unveil preclinical period and prodromal stages of Alzheimer's disease (AD). The mild cognitive impairment (MCI) is characterized by significant memory and/or other cognitive domains impairments, and is often considered the prodromal phase of AD. The cerebrospinal fluid (CSF) levels of β-amyloid (βA), total tau (t-tau), and phosphorylated tau (p-tau) have been used as biomarkers of AD albeit their significance as indicators during early stages of AD remains far from accurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 107 publications
(149 reference statements)
1
10
0
Order By: Relevance
“…Bivariate relationships (depicted as dotted lines, along with correlation coefficient r ) differed depending on the p-tau range of concentrations (<50, 50–80, and > 80 pg/ml). B) Bivariate plot of In-Out-test punctuations and factor scores for principal component 1 from multivariate analyses of ER-signalosome and scaffolding proteins (modified from reference [ 29 ]). C) Bivariate plot of In-Out-test punctuations and factor scores for principal component 1 from multivariate analyses of trace metals, lipoxidative metabolites, antioxidant/detoxifying enzymes (modified from reference [ 92 ]).…”
Section: Neuropsychologymentioning
confidence: 99%
See 3 more Smart Citations
“…Bivariate relationships (depicted as dotted lines, along with correlation coefficient r ) differed depending on the p-tau range of concentrations (<50, 50–80, and > 80 pg/ml). B) Bivariate plot of In-Out-test punctuations and factor scores for principal component 1 from multivariate analyses of ER-signalosome and scaffolding proteins (modified from reference [ 29 ]). C) Bivariate plot of In-Out-test punctuations and factor scores for principal component 1 from multivariate analyses of trace metals, lipoxidative metabolites, antioxidant/detoxifying enzymes (modified from reference [ 92 ]).…”
Section: Neuropsychologymentioning
confidence: 99%
“…As these changes do not necessarily lead to AD-type dementia, the question arises of how these alterations may be predictive of a neurodegenerative outcome. We have observed such alterations in neurolipids (docosahexaenoic acid, docosapentaenoic acid), ER-signalosome multiprotein complex (including the estrogen receptor alpha (Erα), insulin-like growth factor 1 receptor beta (IGF-1Rβ), prion protein (PrP), voltage-dependent anion channel 1 (VDAC1)), scaffolding proteins (caeolin-1 and flotilin-1), trace biometals (Cu, Se, Zn, Mn) and related molecules (transferrin), antioxidant/detoxifying enzyme activities (superoxide dismutase (SOD), glutathione peroxidase 4, glutathione-S-transferase, butyrylcholinesterase), and also in oxidative stress-related metabolites (malondialdehyde) reflected in the CSF of individuals diagnosed SMC or MCI [ 29, 92 ]. The essential concept of these observations is that these changes reflect biochemical changes occurring in the brain parenchyma in aged individual during initial stages of cognitive alterations, irrespective of whether subjects will develop any type of dementia.…”
Section: Neuropsychologymentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that imbalances in various neuroendocrine related systems, such as the HPA axis, HPG axis, insulin and brain-gut axis, can be observed in people with early stage AD, while related hormone therapy has been proved to achieve better results only in the early stages of aging ( 84 , 85 ). This suggests that the intervention of AD through the neuroendocrine related axis needs to be carried out before the irreversible accumulation of neurotoxic substances, and there is still a large gap in the relevant early drug treatment in western medicine intervention.…”
Section: Manuscript Formattingmentioning
confidence: 99%